Meta‑analysis of genetic parameter estimates of residual feed intake and of its component traits in cattle - Del Claro, Ana Cecília; Mercadante, Maria Eugênia Zerlotti; Silva, Josineudson Augusto II Vasconcelos (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to estimate, by meta‑analysis, the heritability (h2) and the genetic (rg) and phenotypic (rf) correlations of residual feed intake (RFI), and of its component traits in beef cattle from 19 breeds or genetic groups. Twenty‑two scientific papers published from 1963 to 2011, from eight countries, totaling 52,637 cattle of ages from 28 days up to slaughter, were evaluated. The estimates of RFI, dry matter intake (DMI), average daily gain (ADG) and metabolic weight (BW0.75) were weighted by the inverse of sample variance. The variation between studies of h2 for each trait was analyzed by weighted least squares. The effects of sex, country and breed were significant for h2 of RFI, explaining 67% of variation between studies. For DMI, country and breed effects were significant and explained 96% of variation. Pooled estimates of h2 were: 0.255±0.008, 0.278±0.012, 0.321±0.015, and 0.397±0.032 for RFI, DMI, ADG and BW0.75, respectively. Pooled estimates of genetic and phenotypic correlations were low between RFI and ADG and between RFI and BW0.75 (from ‑0.021±0.034 to 0.025±0.035), and moderate between RFI and DMI (0.636±0.035 and 0.698±0.041) and between DMI, ADG and BW0.75 (0.441±0.062 to 0.688±0.032). The trait RFI has lower heritability estimates than its components.